Cancer Screening and Cancer Treatment in Kidney Transplant Recipients - Bigotte Vieira, Miguel (2024)
Publisher Copyright: Copyright © 2024 The Author(s). Published by Wolters Kluwer Health, Inc. on behalf of the American Society of Nephrology.